Value co-creation in public social media at different stages of the new product development process: A case study of a Polish clothes manufacturer - Beata Piątkowska (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2022)
This study contributes to the value co-creation theory in the context of the new product development process. The aim of this study is a comparison of interactions that lead to creation of value on public social media. The considered interactions are at different stages of the new product development process: an idea generation and product development (crowdsourcing) and post-launch (product offerings). The place where interactions take place is Facebook fan page of a Polish clothes manufacturer. The DART model of value co-creation is the framework of the comparison. The results show that interactions at the stage of ideation and product development phase attracted more attention from the social media users than post-launch ones. Interactions at the stage of idea generation phase encouraged social media users to communicate with other social media users. It was rare with post-launch activities in the form of product offering. The study is qualitative, based on a case study of a Polish clothes manufacturer with the use of an in- depth interview and netnography.
Keywords: M30; M31; 650; value co-creation; crowdsourcing; new product development; social media